Renewable bio-ass and wastes to energy, economic goods and services: A review - Samra, J.S. Gaur, Neetu. and Mangal, S.K. (Man & Development)
Energy has been a primary force of socio-economic and environmental transformations will continue to be so and its excessive consumption is harmful to environment. taffies on solar and wind energy are low but can only be produced for for 5-6 hours during day time liquid and gaseous bio fuels are produced for 24 hours in a year, their storage and distribution is economically viable as well environmentally sustainable. - Reproduced
Keywords: Advanced technologies, Renewable energy potentials, Waste to wealth, Investment portfolios,Environmental externalities , Incentives, Debt financing, Green financing, Case of doing business